Internet Addiction Markers of Mental Health Disorders Among University Youth - Hulias, Inesa A.; Kariyev, Adlet D.; Zhandykeyeva, Gulnar Ye.; Smolinska, Olesia Ye.; Kulbida, Svitlana V.; Kolly-Shamne, Anzhelika V. (Wydawnictwo Adam Marszałek, 2026)
The study aims to determine the internet addiction markers of mental health disorders among university youth. Statistically significant differences were identified among the three groups based on the severity of internet addiction – low, medium, and high. Differences were found in all studied parameters based on the grouping variables “internet addiction” and “prob lematic use of mobile phone”. It was summarized that external markers of mental health showed direct correlations, while internal markers showed inverse correlations with internet addiction at a high level of significance.
Keywords: educational process, artificial intelligence, mental state, stress, gender differentiation